Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

(ii) 2/√x + 3/√y = 2 4/√x + 9/√y = -1

(ii) 2/√x + 3/√y = 2

4/√x + 9/√y = -1

Grade:12th pass

1 Answers

Pawan Prajapati
askIITians Faculty 8740 Points
4 months ago
Solution: Substituting 1/√x = m and 1/√y = n in the given equations, we get 2m + 3n = 2 ………………………..(i) 4m – 9n = -1 ………………………(ii) Multiplying equation (i) by 3, we get 6m + 9n = 6 ………………….…..(iii) Adding equation (ii) and (iii), we get 10m = 5 m = 1/2…………………………….…(iv) Now by putting the value of ‘m’ in equation (i), we get 2×1/2 + 3n = 2 3n = 1 n = 1/3 m =1/√x ½ = 1/√x x = 4 n = 1/√y 1/3 = 1/√y y = 9 Hence, x = 4 and y = 9

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free